Influence of the mode of application of universal adhesive systems on adhesive properties to fluorotic enamel - Andres Felipe Millan CARDENAS; Ana ARMAS-VEJA; Juan Pablo RODRIGUEZ VILLARREAL; Fabiana Suelen Figueredo de SIQUEIRA; Luana Paraiso MUNIZ; Veridiana Silva CAMPOS; Alessandra REIS; Alessandro Dourado LOGUERCIO
Abstract The objective of this study is to compare the resin-enamel bond strength (mμSBS), in-situ degree of conversion (DC), and the enamel-etching pattern (SEM/EDX) of universal adhesive systems when applied to sound and fluorotic enamel. Ninety-eight human molars were sectioned into 4 parts and divided into 24 groups according to 1) enamel surface (sound or fluorotic enamel), 2) adhesive system (Clearfil Universal Bond [CUB], Futurabond U [FBU], iBond Universal [IBU], and Scotchbond Universal [SBU]), and 3) application mode (etch-and-rinse [ER], active self-etch [Active-SE], and passive self-etch [Passive-SE]). Specimens were stored at 37 °C, for 24 hours and tested at 1.0 mm/min (μSBS). Enamel-resin interfaces were evaluated for in-situ DC. The enamel-etching pattern was evaluated under a SEM/EDX. Data from mμSBS and in-situ DC was analyzed using a three-way ANOVA and Tukey's test at 5 % level of significance. For all adhesives, the ER resulted in a statistically significant higher mean mμSBS than the passive-SE in both substrates (p < 0.001). For all adhesives, active-SE resulted in mean mμSBS (p > 0.31) and in-situ DC (p > 0.45) that were statistically similar to those obtained with the ERs in both substrates. A statistically significant, higher mean mμSBS and in-situ DC were obtained in sound enamel (p < 0.001) than in fluorotic enamel. In general, SBU showed higher mean values for mμSBS and in-situ DC compared to those of CUB and IBU (p < 0.001). ER and active-SE showed the deepest enamel-etching pattern in both substrates. A higher amount of fluor was observed in fluorotic enamel. The active application of universal adhesives in the SE-mode may be a viable alternative to increase the adhesive properties in sound and fluorotic enamel.